Digital skills of pupils aged 6–9 – children’s and adults’ perspective - Agnieszka Iwanicka (Problemy Wczesnej Edukacji)
In this article, I presented the results of the research aimed at identifying how early school age children create their digital skills. Despite the fact that the topic of digital skills seems to be an empirically well-recognized area, there is still relatively little research on children aged 6–9 years. I presented the conducted research both from the perspective of a child and an adult: digital experts and teachers. I conducted both qualitative research (in-depth interview with thirty children and ten digital experts) and quantitative research (survey with 717 teachers). Such a confrontation of three perspectives allowed for a full view of the digital world of the child. The research showed the thinking community of children and digital experts, and the opposing (in many aspects) early childhood education teacher’s way of thinking.